"Not a Word Was Said Ever Again": Silence and Speech in Women's Oral History Accounts of Sexual Harassment. Issue 1 (2nd January 2023) - Freedman, Estelle B.
ABSTRACT: Oral history collections provide rich evidence for understanding sexual harassment in the era before that term applied to unwanted sexual advances in schools and workplaces. Close reading of both speech and silence about sexual harassment in oral histories also illuminates women's historical reluctance to recall or make public their experiences of sexual violence. Drawing on a large dataset of digitized oral history collections, this essay maps women's memories of, and responses to, sexual harassment from the late 1930s through the mid-1970s. Whether they minimized the problem or identified with it, the narrators who addressed sexual harassment typically emphasized women's personal responsibility and the lack of institutional accountability. Their recollections also reveal a range of individual forms of resistance that women employed before feminists named or laws prohibited sexual harassment.